2022
DOI: 10.29271/jcpsp.2022.04.455
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold Videocapillaroscopy in Patients with COVID-19-associated Pneumonia in Intensive Care Units

Abstract: Objective: To compare patients with COVID-19 in intensive care units (ICUs) to healthy controls using nailfold videocapillaroscopy (NVC), offering standardised findings about micro-circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…The alterations in capillary density and microvascular flow parameters were substantially comparable with the results of the patients with severe SARS-CoV-2 pneumonia admitted to the ICU but not subjected to VV-ECMO found by Damiani et al [37,39]. Furthermore, Carsetti et al found a relationship between D-dimer values and changes in capillary density, a finding also found by Karahan et al, in patients with severe COVID-19 admitted to intensive care, who were compared with a healthy control group [29].…”
Section: Nvc Vs Other Methods To Evaluate Microcirculationsupporting
confidence: 79%
See 2 more Smart Citations
“…The alterations in capillary density and microvascular flow parameters were substantially comparable with the results of the patients with severe SARS-CoV-2 pneumonia admitted to the ICU but not subjected to VV-ECMO found by Damiani et al [37,39]. Furthermore, Carsetti et al found a relationship between D-dimer values and changes in capillary density, a finding also found by Karahan et al, in patients with severe COVID-19 admitted to intensive care, who were compared with a healthy control group [29].…”
Section: Nvc Vs Other Methods To Evaluate Microcirculationsupporting
confidence: 79%
“…In patients with acute SARS-CoV-2 infection, the main changes are an increase in capillary size (i.e., an enlarged capillary), although never the presence of true giant capillaries, together with edema, microhemorrhages, and thromboembolic phenomena [21,29]. The presence of hemosiderin deposits and capillary alterations are in keeping with the pathophysiological alterations of COVID-19 known to us today, in particular endothelium involvement [7,8].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The lumen size of skin arterio-venous anastomoses (AVA) is regulated exclusively by neurogenic mechanisms, so we can assume that they also expand amidst the decrease of neurogenic tone. The dilation of AVA leads to arterio-venous shunting of the blood bypassing the capillary channel, which explains the significant decrease of I mn , a decrease of the number of functioning capillaries [13,14], reduction of perfusion (I m ) and venular overflow due to arterial blood discharge that in its turn leads to the dilation of venules [40,41] and a significant increase of the amplitude of respiratory-driven blood flow oscillations amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread prevalence of the disease and the incidence of cardiovascular complications, as well as the proven extensive involvement of microvasculature in pathological processes, only very few papers have been published to date on the noninvasive assessment of blood microcirculation after COVID-19 [12][13][14].…”
Section: Introductionmentioning
confidence: 99%